In situ fluorescence yield soft X-ray absorption spectroscopy of electrochemical nickel deposition processes with and without ethylene glycol. Issue 17 (5th April 2022) - Yamaguchi, Akinobu; Akamatsu, Naoya; Saegusa, Shunya; Nakamura, Ryo; Utsumi, Yuichi; Kato, Masaru; Yagi, Ichizo; Ishihara, Tomoko; Oura, Masaki
Abstract : Schematic drawing of electrochemical reactions of the Pt-coated SiC electrode, which separates the vacuum and the solution containing Ni 2+ and ethylene glycol, in our spectro-electrochemical setup for the FY-XAS. Abstract : The electrochemical Ni deposition at a platinum electrode was investigated in a plating nickel bath in the presence and absence of ethylene glycol (EG) using fluorescence yield soft X-ray absorption spectroscopy (FY-XAS) in the Ni L2, 3 -edge and O K-edge regions under potential control. At ≤+0.35 V vs. the reversible hydrogen electrode (RHE), the electrochemical Ni deposition was detected by the Ni L2, 3 -edge FY-XAS in the presence of EG whereas almost no such event was observed in the absence of EG. A drastic decrease of FY-XAS intensities in the O K-edge region was also observed in the presence of EG at >+0.35 V vs. RHE, suggesting that the nano-/micro-structured Ni deposition initiated by the removal of water molecules occurs on the Pt electrode. The complex formation of Ni 2+ with EG and the adsorption of EG on the Ni surface could play an important role in the Ni deposition. This study demonstrates that the in situ FY-XAS is a powerful and surface-sensitive technique to understand (electro)chemical reactions including polyol synthesis and electrocatalysis at solid–liquid interfaces.